2022
DOI: 10.3390/ijms23179899
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Landscape of Chronic Myeloid Leukemia K562 Cells Overexpressing the Tumor Suppressor Gene PTPRG

Abstract: This study concerns the analysis of the modulation of Chronic Myeloid Leukemia (CML) cell model K562 transcriptome following transfection with the tumor suppressor gene encoding for Protein Tyrosine Phosphatase Receptor Type G (PTPRG) and treatment with the tyrosine kinase inhibitor (TKI) Imatinib. Specifically, we aimed at identifying genes whose level of expression is altered by PTPRG modulation and Imatinib concentration. Statistical tests as differential expression analysis (DEA) supported by gene set enri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…To further evaluate the physical regulatory connection between identified CNEs and their precise target promoter, we used Hi‐C data for human embryonic stem cells (H1‐ESC), K562 cells, and GM12878 cells from the 3D genome browser (http://3dgenome.fsm.northwestern.edu/view.php) (Figure 2b and Supporting Information S1: Figures S3 and S4A,B) (Wang et al, 2018). These cell lines are reported to express TRPS1 TF (Joung et al, 2023; Lombardi et al, 2022). The Hi‐C data for H1‐ESC and k562 cells revealed that the TRPS1 gene is embedded in a domain with enhanced interactions compared to surrounding chromatin regions (Figure 2b; Supporting Information S1: Figure S4B).…”
Section: Resultsmentioning
confidence: 99%
“…To further evaluate the physical regulatory connection between identified CNEs and their precise target promoter, we used Hi‐C data for human embryonic stem cells (H1‐ESC), K562 cells, and GM12878 cells from the 3D genome browser (http://3dgenome.fsm.northwestern.edu/view.php) (Figure 2b and Supporting Information S1: Figures S3 and S4A,B) (Wang et al, 2018). These cell lines are reported to express TRPS1 TF (Joung et al, 2023; Lombardi et al, 2022). The Hi‐C data for H1‐ESC and k562 cells revealed that the TRPS1 gene is embedded in a domain with enhanced interactions compared to surrounding chromatin regions (Figure 2b; Supporting Information S1: Figure S4B).…”
Section: Resultsmentioning
confidence: 99%
“… 13 More recently, our group had documented that PTPRG overexpression induce a global modification of gene expression and pinpoint the critical role of transcription factor in the reprogramming of CML cells. 15 …”
Section: Introductionmentioning
confidence: 99%
“…13 More recently, our group had documented that PTPRG overexpression induce a global modification of gene expression and pinpoint the critical role of transcription factor in the reprogramming of CML cells. 15 Ismail et al 16 reported that the restoration of PTPRG protein expression on neutrophil-white blood cells following TKIbased therapy in CML patients was greater in optimal response patients when compared to those who failed treatment. Additionally, higher expression of PTPRG was observed with nilotinib treatment when compared to IM.…”
Section: Introductionmentioning
confidence: 99%